Winter behavior of Saimaa ringed seals: Non-overlapping core areas as indicators of avoidance in breeding females - Niemi, Marja; Liukkonen, Lauri; Koivuniemi, Meeri; Auttila, Miina; Rautio, Anni; Kunnasranta, Mervi
Article e0210266 2019